Neisseria gonorrhoeae and Chlamydia trachomatis coinfection in a 20-year-old man with recurrent urethritis: a case report - Prawarni, Vidyadhari Puspa; Prameshwara, Almarissa Ajeng; Susetiati, Devi Artami; Nuryastuti, Titik (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2024)
Introduction: Neisseria gonorrhoeae and Chlamydia trachomatis are the two pathogens most commonly reported to cause sexually transmitted infections (STIs) worldwide. Coinfection between these two pathogens has been widely reported, but the incidence is still rarely reported due to challenges in diagnosis to prove the involvement of the two pathogens simultaneously. The molecular diagnostic approach is an effective option for this case and optimizing this method will able to help clinicians deciding management for the patients and prevent the spreading of the disease. This study aimed to present a case of N. gonorrhoeae and C. trachomatis coinfection in a 20-year-old man with recurrent urethritis. Case Description: A 20-year-old man presented to the Dermatology and Venereology clinic at Dr. RSUP. Sardjito with purulent discharge from the penis started a week prior. From the anamnesis and physical examination, the doctors suspected this patient with N. gonorrhoeae infection. N. gonorrhoeae was detected by microscopic examination, culture, and Real-Time Polymerase Chain Reaction (RT-PCR) examination, while C. trachomatis was also detected in RT-PCR. The patient was treated with azithromycin 1-gram single dose and cefixime 400 mg single dose. Discussion: The World Health Organization (WHO) reported that the incidence of STIs is always increasing. Most STIs are usually asymptomatic, but it can be presented as urethritis in male patients. For females, it can be given as leucorrhoea, pelvic inflammatory disease (PID), or other pregnancy complications. N. gonorrhoeae and C. trachomatis are the two main pathogens always reported annually and often found as coinfection. Due to the virulence factors of these bacteria, N. gonorrhoeae and C. trachomatis are very hard to diagnose with conventional culture methods, and the molecular approach is now an effective option to detect them and help prevent recurrence. Conclusion: Coinfection of N. gonorrhoeae and C. trachomatis is a case that is quite often encountered in clinical practice, but the incidence is rarely reported due to supporting examination methods to help confirm the presence of these two microorganisms are still limited. In cases of suspected infection by N. gonorrhoeae, C. trachomatis, or both simultaneously, the most recommended microbiological examination is to use molecular diagnostics such as PCR.